Improving depth resolution of ultrasonic phased array imaging to inspect aerospace composite structures - Mohammadkhani, Reza; Fragonara, Luca Zanotti; Padiyar M, Janardhan; Petrunin, Ivan; Raposo, João; Tsourdos, Antonios; Gray, Iain (MDPI, 2020)
In this paper, we present challenges and achievements in development and use of a compact ultrasonic Phased Array (PA) module with signal processing and imaging technology for autonomous non-destructive evaluation of composite aerospace structures. We analyse two different sets of ultrasonic scan data, acquired from 5 MHz and 10 MHz PA transducers. Although higher frequency transducers promise higher axial (depth) resolution in PA imaging, we face several signal processing challenges to detect defects in composite specimens at 10 MHz. One of the challenges is the presence of multiple echoes at the boundary of the composite layers called structural noise. Here, we propose a wavelet transform-based algorithm that is able to detect and characterize defects (depth, size, and shape in 3D plots). This algorithm uses a smart thresholding technique based on the extracted statistical mean and standard deviation of the structural noise. Finally, we use the proposed algorithm to detect and characterize defects in a standard calibration specimen and validate the results by comparing to the designed depth information.
Keywords: ultrasonic NDE; autonomous inspection; ultrasonic phased array; composite materials; depth resolution; defect sizing; NDT